2020
DOI: 10.3390/nu12061678
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence of Benefits to Mood and Working Memory from Lipidated Curcumin in Healthy Older People: A 12-Week, Double-Blind, Placebo-Controlled, Partial Replication Study

Abstract: Curcumin (a flavonoid isolated from turmeric) affects several processes involved in neurocognitive aging. We have previously reported that short term (4-weeks) administration of a highly bioavailable curcumin preparation (Longvida©) improved working memory and reduced fatigue and stress reactivity in a healthy older cohort. The present trial (ACTRN12616000484448) was a partial replication study, evaluating similar effects at 4 and 12-weeks Longvida© supplementation. A double-blind, placebo-controlled, parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…The observed mood-enhancing effect of curcumin, i.e., increase in vigour, is consistent with previous studies study by Cox et al, which found reductions in fatigue following 4 and 12 weeks of supplementation in older non-depressed adults [ 9 , 10 ]. Furthermore, Cox et al found significant reductions in tension, anger, confusion and TMD following supplementation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The observed mood-enhancing effect of curcumin, i.e., increase in vigour, is consistent with previous studies study by Cox et al, which found reductions in fatigue following 4 and 12 weeks of supplementation in older non-depressed adults [ 9 , 10 ]. Furthermore, Cox et al found significant reductions in tension, anger, confusion and TMD following supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Cox et al found significant reductions in tension, anger, confusion and TMD following supplementation. However, these effects were only short-term and were not sustained after 12 weeks of supplementation [ 10 ]. In both studies, Cox et al supplemented their participants with 400 mg Longvida curcumin (80 mg curcumin) once a day; however, we chose to give this dose twice daily to ensure a sustained level of curcumin in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations